Robert H. Goetz: A Heritage of Coronary Artery Bypass Surgery (Bangladesh Heart Journal, 2019)
Robert H. Goetz performed the first successful clinical coronary artery bypass operation on May 2, 1960. He used a nonsuture technique to connect the right internal mammary artery to the coronary artery by means of a modified Payr’s cannula made of tantalum. The patency of the anastomosis was demonstrated angiographically and the patient remained free of angina pectoris for 1 year. It was an important and brave step forward, a step that was far ahead of its time. But unfortunately, his pioneering work was not appreciated properly.Bangladesh Heart Journal 2019; 34(2) : 132-136